Rethinking the Arts Business (Museum, Gallery, Theater) Strategy: Study Case Ciputra Artpreneur - Hilary, Andri; Anggoro, Yudo (The Indonesian Journal of Business Administration, 2019)
Abstract - Ciputra Artpreneur is one of the subsidiaries owned by Ciputra Group, that serves as the CSR (Corporate Social Responsibility) of the company to concentrate in the arts business. It was built as a dedicated arts center that consists of the museum, the gallery and the theater. As the first of its kind, Ciputra Artpreneur’s challenge is to build the sustainability of itself in the disruptive era. Ciputra Artpreneur are in the state where it relies on the arts appreciation levels of Indonesian public, and in the era of competition where competitors can be considered unknown, thus making Ciputra Artpreneur’s challenge is to implement efficient and sustainable business strategy. This research will be conducted using mixed method, where the objective of this research is to identify the best business strategy and improvement needed by Ciputra Artpreneur to achieve sustainability, as well as to manage the expectations of the public. Research results show that Ciputra Artpreneur need to improve and enrich the capabilities and growth of employees as the core in handling the business units, and externally to do the integration between the three business units, and producing or bringing constant events that can strengthen Ciputra Artpreneur as a brand and as a dedicated arts center in Jakarta, Indonesia. Ciputra Artpreneur also has to have a two to five-year plan, as a guidance in establishing the goals of each year to reach sustainability in the future. The competition is getting fiercer, as many competitors are starting to see the arts business as a new potential line of business. Now is the right time for Ciputra Artpreneur to improve its strategy and implement new ideas and ways to achieve sustainability in the future.Keywords: Arts business, business strategy, sustainability, content management, improvement